Mathematical analysis of maximum power generated by photovoltaic systems and fitting curves for standard test conditions - Gabriel, Luiz Roberto Almeida [UNESP]; Viais Neto, Daniel dos S.; Cremasco, Camila P. [UNESP]; Seraphim, Odivaldo J.; Caneppele, Fernando de L. (Soc Brasil Engenharia Agricola, 2012)
The rural electrification is characterized by geographical dispersion of the population, low consumption, high investment by consumers and high cost. Moreover, solar radiation constitutes an inexhaustible source of energy and in its conversion into electricity photovoltaic panels are used. In this study, equations were adjusted to field conditions presented by the manufacturer for current and power of small photovoltaic systems. The mathematical analysis was performed on the photovoltaic rural system I- 100 from ISOFOTON, with power 300 Wp, located at the Experimental Farm Lageado of FCA/UNESP. For the development of such equations, the circuitry of photovoltaic cells has been studied to apply iterative numerical methods for the determination of electrical parameters and possible errors in the appropriate equations in the literature to reality. Therefore, a simulation of a photovoltaic panel was proposed through mathematical equations that were adjusted according to the data of local radiation. The results have presented equations that provide real answers to the user and may assist in the design of these systems, once calculated that the maximum power limit ensures a supply of energy generated. This real sizing helps establishing the possible applications of solar energy to the rural producer and informing the real possibilities of generating electricity from the sun.

A eletrificação rural é caracterizada pela dispersão geográfica da população, baixo consumo, alto investimento por consumidor e elevado custo operacional. Por outro lado, a radiação solar constitui-se numa inesgotável fonte energética, e para sua conversão em energia elétrica são utilizados painéis fotovoltaicos. Neste trabalho, foram determinadas equações ajustadas às condições de campo apresentadas pelo fabricante para corrente e potência de sistemas fotovoltaicos de pequeno porte. A análise matemática foi feita sobre o sistema fotovoltaico rural I-100 da ISOFOTON, com potência de 300 Wp, localizado na Fazenda Experimental Lageado da FCA/UNESP. Para o desenvolvimento de tais equações, procurou-se estudar o circuito elétrico de células fotovoltaicas, aplicar os métodos numéricos iterativos para a determinação de parâmetros elétricos e analisar possíveis erros na adequação das equações existentes da literatura à realidade. Sendo assim, foi proposta a simulação de um painel fotovoltaico por meio de equações matemáticas que foram ajustadas segundo os dados de radiação locais. Os resultados apresentam equações que fornecem respostas reais para o usuário e podem auxiliar no dimensionamento destes sistemas, uma vez que a potência máxima calculada garante um limite de fornecimento da energia gerada. Este real dimensionamento auxilia a determinação das possíveis aplicações da energia solar para o produtor rural, informando as possibilidades reais de geração de energia elétrica pelo Sol.
Modelo matemático da potência máxima gerada por sistemas fotovoltaicos e curvas de ajuste às condições de teste em campo
Keywords: rural electrification; photovoltaic cells; numerical methods